Determination and Characterization of Lycopene Compounds from N-Hexane Fraction of Tomato Fruit (Solanum Lycopersocum Grandyfolium) by using Fourier Transform Infrared and UV-Vis Spectrophotometry - Arfiani Nur; Hajrah Hajrah; Asriani Ilyas; Aisyah Aisyah; Maria Cecilia Lezama Escalante (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Determination and characterization of the lycopene content of the n-hexane fraction from potato-leaved tomato (Solanum lycopersicum grandyfolium) using Fourier transform infrared (FTIR) spectrophotometry and UV-Vis spectrophotometry. This study aims to determine the levels and characterization of lycopene compounds from potato-leaved tomato fruit using FTIR and UV-Vis spectrophotometers. The methods in this research include maceration, liquid-liquid extraction, crystallization with antisolvent, chromatography with three eluent systems, identification of lycopene compounds, and characterization of lycopene compounds using FTIR and UV-Vis. The results showed the presence of lycopene compounds based on the spectrum with absorption peaks at wave numbers 2924, 18 cm-1 and 2863, 66 cm-1 indicating C-H (stretching); 1637, 43 cm-1 indicating C=C alkene; and the wave numbers of 1461, 63 cm-1 and 1422, 46 cm-1 indicating the presence of a CH2 (bending) functional group. The results of UV-Vis spectrophotometric characterization showed the presence of lycopene compounds at three main wavelengths, namely at 445, 467, and 500 nm. The level of lycopene compounds produced from the n-hexane extract of potato-leaved tomato fruit was 7.25 mg/gram